The Moderator Role of Age in the Unified Theory of Acceptance and Use of Technology: Intention to Use Internet Banking in Sudan - Omer, Adam Haroun; Adam, Fathi Ahmed Ali (Journal of Economic, Administrative and Legal Sciences, 2020)
The objective of this paper is to identify the moderator role of age in the unified theory of acceptance and use of technology: Intention to Use internet banking in Sudan. To achieve this objective the researchers adopted the questionnaire to data collection. A total of 375 questionnaires are distributed 207 respondents are well-responded. Used SPSS, Excel, SmartPLS to analysis the data collected. The results indicate that the age (34yrs and less) does prove as a moderator in effort expectancy, social influence, and intention to use Internet banking. Also, the age generally does not prove as a moderator in internet banking awareness and intention to use internet banking. The study recommended to study the effect of income and education level on acceptance of e-banking services.
Keywords: the unified theory of acceptance and use of technology; UTAUT; Internet Banking; Sudan; Internet Banking Awareness